2018
DOI: 10.1371/journal.pone.0209620
|View full text |Cite
|
Sign up to set email alerts
|

Conformity in numbers—Does criticality in social responses exist?

Abstract: Within this paper we explore the idea of a critical value representing the proportion of majority members within a group that affects dramatic changes in influence targets’ conformity. We consider the threshold q-voter model when the responses of the Willis-Nail model, a well-established two-dimensional model of social response, are used as a foundation. Specifically, we study a generalized threshold q-voter model when all basic types of social response described by Willis-Nail model are considered, i.e. confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 50 publications
(106 reference statements)
1
28
0
Order By: Relevance
“…Discontinuous phase transitions do not appear even for highly connected networks. This result is consistent with the result obtained for the generalized threshold q-voter model [21,28], as described above.…”
Section: Binary Opinion Models With a Single-flip Dynamicssupporting
confidence: 93%
See 4 more Smart Citations
“…Discontinuous phase transitions do not appear even for highly connected networks. This result is consistent with the result obtained for the generalized threshold q-voter model [21,28], as described above.…”
Section: Binary Opinion Models With a Single-flip Dynamicssupporting
confidence: 93%
“…Another possibility to obtain a discontinuous phase transition has been recently suggested within the generalized threshold q-voter model, in which two types of nonconformity were introduced simultaneously [28]. It has been shown that discontinuous phase transition could be obtained even without independence if only the threshold for anticonformity would be smaller than for conformity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations